The peaceful conspiracy: bond markets and international relations during the Pax Britannica - Flandreau, Marc; Flores, Juan H. (International Organization, 2012)
This article provides foundations to K. Polanyi's famed argument that monopoly power in the global capital market served as an instrument of peace during the Pax Britannica (1815-1914). We focus on the role of intermediaries and certification. We show that when information and enforcement are imperfect, there is scope for the endogenous emergence of 'prestigious' intermediaries who enjoy a monopoly position and as a result, control government actions. They can implement conditional lending: they subject the distribution of credit to the adoption of peaceful policies. Prestigious intermediaries act that way because of their concern with maintaining an unblemished track record when wars increased risks of default. Our analysis, which brings together insights from different disciplines, provides a significant extension to, and departure from, recent research on how countries accumulate reputational capital.
Keywords: Pax-Britannica; United Kingdom; bond markets; economic history; global capital market (1815-1914); international relations